Attitudes Towards Corruption and Women in Children’s Literature and Detective Fiction: A Parallel between Zheng Yuanjie and Zijin Chen - Aiqing Wang (English Department FBS UNP, 2021)
In this article, I explore male writers’ attitudes towards corruption and women in fairy tales and detective novels, by means of hermeneutically scrutinising works of Zheng Yuanjie, the illustrious ‘King of Fairy Tales’, as well as Zijin Chen, the ‘Chinese Keigo Higashino’. Anti-corruption is a prevalent and preponderant theme in both writers’ creation, yet their depictions of barbarous extrajudicial punishment for government officials’ misdeeds allude to karmic retribution and are prone to expatiation in graphic detail. Therefore, some of their fiction appertaining to anti-corruption can be regarded as ‘feel-good writing’ in essence. Furthermore, the writing of Zheng and Chen is sometimes featured by lack of feminist consciousness, in that a proportion of their works manifest gender stereotypes, which can also be attested in other male writers’ fairy tales and detective novels.